2023
DOI: 10.1021/acsami.2c20004
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Recovery of the Electrochemically Degraded LiCoO2/Li7La3Zr2O12:Al,Ta Interface in an All-Solid-State Lithium Battery

Abstract: All-solid-state lithium batteries are promising candidates for next-generation energy storage systems. Their performance critically depends on the capacity and cycling stability of the cathodic layer. Cells with a garnet Li7La3Zr2O12 (LLZO) electrolyte can show high areal storage capacity. However, they commonly suffer from performance degradation during cycling. For fully inorganic cells based on LiCoO2 (LCO) as cathode active material and LLZO, the electrochemically induced interface amorphization has been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…As there is in fact Al (diffused from alumina substrate) existing in the LCO phase of the cathode, the impact of Al on the battery performance requires further investigation. In this regard, additional experiments by sintering on different substrates can be done for a comparison to evaluate the effect of Al-doping in LCO for the LCO-garnet composite cathodes …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As there is in fact Al (diffused from alumina substrate) existing in the LCO phase of the cathode, the impact of Al on the battery performance requires further investigation. In this regard, additional experiments by sintering on different substrates can be done for a comparison to evaluate the effect of Al-doping in LCO for the LCO-garnet composite cathodes …”
Section: Resultsmentioning
confidence: 99%
“…In this regard, additional experiments by sintering on different substrates can be done for a comparison to evaluate the effect of Al-doping in LCO for the LCO-garnet composite cathodes. 45 Other degradation contributions could relate to the anode. As shown in our previous study, the Coulombic efficiency of the LFP-based SSLBs with indium anode was 96−98%, while the one of SSLBs with Li anode was 99%.…”
Section: Tape Casting Of Lco-llzto Composite Cathodesmentioning
confidence: 99%
“…[47] Ihrig et al reported that amorphous interphases are formed on the interfaces between LCO and LLZT after charge/discharge cycles, [61] which could be recovered by thermal treatment. [62] It is known that element interdiffusion is induced by electrochemical processes for sulfide-based ASSBs. [63] However, in our studies, such interphases could not be confirmed even after six cycles (Figure 4).…”
Section: Deterioration Of the Cellmentioning
confidence: 99%
“…7,8 Whereas for the Li | LLZO interface significant improvements have been achieved, 9 the cathode side still suffers from technical challenges such as poor contact between the LLZO and the cathode or contact loss during cycling due to volume changes within the cathode. 10,11,12,13,14 A stable interface contact is a key requirement for high initial discharge capacities, this however, requires high temperature processing. To form sufficient bonding between the individual components in an all-oxide cathode composed by LLZO and LiCoO2 (LCO) temperatures from 600 to 1050 °C are required (see Table 1).…”
Section: Introductionmentioning
confidence: 99%